Genetic population data of 12 STR loci of the PowerPlex (R) Y system in the state of São Paulo population (Southeast of Brazil) - Gois, C. C.; Martins, J. A. [UNESP]; Pereira, G. A. [UNESP]; Freschi, A. [UNESP]; Paneto, G. G. [UNESP]; Alvarenga, Vera Lucy de Santi [UNESP]; Cicarelli, Regina Maria Barretto [UNESP]; Hirata, M. H.; Oliveira, R. N. (Elsevier B.V., 2008)
Allele frequency distributions and population data for 12 Y-chromosomal short tandem repeats (STRs) included in the PowerPlex (R) Y Systems (Promega) were obtained for a sample of 200 healthy unrelated males living in S (a) over tildeo Paulo State (Southeast of Brazil). A total of 192 haplotypes were identified, of which 184 were unique and 8 were found in 2 individuals. The average gene diversity of the 12 Y-STR was 0.6746 and the haplotype diversity was 0.9996. Pairwise analysis confirmed that our population is more similar with the Italy, North Portugal and Spain, being more distant of the Japan. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Y-chromosome STR; genetic population data; S(a)over-tildeo paulo; Brazil